Let X and Y be jointly continuous with joint probability density function
$$f_{X,Y}(x,y)=\frac{1}{x},0\leq y\le x\le1$$
Find the pdf of $Z=X+Y$

Here is my solution:
$$F_Z(z)=P(Z\leq z)=P(X+Y\leq z)$$
$$=\int_{-\infty}^{\infty}P(X+Y\leq z|X=x)f_X(x)dx$$
$$=\int_{-\infty}^{\infty}P(Y\leq z-x)f_X(x)dx$$
since $f_X(x)=1$, $f_Y(y)=-ln(y)$, and $F_Y(y)=y-yln(y)$,
$$=\int_{0}^{1}(z-x)-(z-x)ln(z-x)dx$$ $$=\frac{z}{2}-\frac{1}{2}+\frac{1}{2}\biggl((z-1)^2ln(z-1)-zln(z)\biggl)$$ So here is the answer I got:
$$f_Z(z)=\frac{d}{dz}F_Z(z)$$ $$=(z-1)ln(z-1)+\frac{z}{2}-\frac{1}{2}ln(z)-\frac{1}{2}$$

I don't think my answer is correct since $0\leq z\leq2$, when I plug 2 into $F_Z(z)$, it doesn't show 1. I'm not sure which part I did wrong.

  • $\begingroup$ What is the support for $f_{X,Y}$? Always indicate the support for these functions. $\endgroup$ – Graham Kemp Sep 6 '18 at 23:50
  • $\begingroup$ I fixed it, thank you! $\endgroup$ – Yibei He Sep 6 '18 at 23:54

Notice, $x,y$ are not independent, so stick with the joint functions. Use the Jaccobian transformation.

Always keep your eye on the supports.

$$\begin{split}f_Z(z) &=\int_\Bbb R f_{X,Z}(x,z)\mathsf d x\\ &= \int_\Bbb R f_{X,Y}(x,z-x) \begin{Vmatrix}\dfrac{\partial (x,z-x)}{\partial (x,z)}\end{Vmatrix}\mathsf d x \\ &=\int_\Bbb R \dfrac 1{x}\mathbf 1_{0\leq (z-x)\leq x\leq 1}\mathsf d x~\\ &= \int_{\max(0,z/2)}^{\min(1,z)} \dfrac 1x \mathbf 1_{z\in(0;2]}\mathrm d x\\ &= \mathbf 1_{z\in(0;1)}\int_{z/2}^{z} \dfrac 1x \mathrm d x+\mathbf 1_{z\in[1;2]}\int_{z/2}^{1} \dfrac 1x \mathrm d x\end{split}$$

  • $\begingroup$ Thank you! Can you explain why the lower bound is max(0,z-1)? Where z-1 comes from? $\endgroup$ – Yibei He Sep 7 '18 at 0:40
  • $\begingroup$ sorry can you explain the Jacobian transformation? $\endgroup$ – Yibei He Sep 7 '18 at 0:56
  • $\begingroup$ It's a chain rule for multivariate change of variables:$f_{U,V}(u,v) = f_{X,Y}(x(u,v), y(u,v))\cdot \left\lvert \dfrac{\partial x(u,v)}{\partial u}\dfrac{\partial y(u,v)}{\partial v}-\dfrac{\partial x(u,v)}{\partial v}\dfrac{\partial y(u,v)}{\partial u}\right\rvert$ $$\begin{align}f_{X,Z}(x,z) &= f_{X,Y}(x, z-x)\cdot \left\lvert \dfrac{\partial x}{\partial x}\dfrac{\partial (z-x)}{\partial z}-\dfrac{\partial x}{\partial z}\dfrac{\partial (z-x)}{\partial x}\right\rvert\\ &= f_{X,Y}(x,z-x)\cdot 1\end{align}$$ $\endgroup$ – Graham Kemp Sep 7 '18 at 3:34

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.